Genetic-Based Susceptibility of a Foundation Tree to Herbivory Interacts With Climate to Influence Arthropod Community Composition, Diversity, and Resilience - Stone, Adrian C.; Gehring, Catherine A.; Cobb, Neil S.; Whitham, Thomas G. (Frontiers in Plant Science, 2018)
Understanding gene by climate interactions among species, especially in the context of extreme events, will help improve predictions of climate change impacts on biodiversity. However, few studies have examined such interactions within a community context. Pinyon pine (Pinus edulis) in the southwestern U.S. shows genetic-based resistance and susceptibility to pinyon needle scale (Matsucoccus acalyptus). We sought to determine if resistance or susceptibility to scale herbivory also influenced the composition of the extended community of 250+ arthropod species, and if this influence would be consistent across consecutive years, an extreme drought year followed by a moderate drought year. Because scale insects alter the architecture of susceptible trees, it is difficult to separate the direct genetic influences of resistance and susceptibility on arthropod communities from the indirect influences of scale-altered tree architecture. To separate these influences, scales were experimentally excluded from susceptible trees for 15 years creating susceptible trees with the architecture of resistant trees, hereafter referred to as scale-excluded trees. Four patterns emerged. 1) In both years, arthropod abundance was 3-4X lower on susceptible trees compared to resistant and scale-excluded trees. 2) Species accumulation curves show that alpha and gamma diversity were 2-3X lower on susceptible trees compared to resistant and scale-excluded trees. 3) There was a significant GxE interaction with year; during extreme drought, arthropod community composition on scale-excluded trees resembled susceptible trees indicating that composition was influenced more by tree genetics. However, under moderate drought, the community on scale-excluded trees resembled the resistant trees indicating that arthropod community composition was influenced more by traits associated with architecture. 4) One year after extreme drought, the arthropod community rebounded sharply. However, there was a greater rebound in arthropod richness and abundance on resistant trees compared to susceptible trees suggesting that resiliency in the arthropod community is also linked to tree genetics. These results argue that genetic influences that affect individual plant-herbivore interactions may directly and indirectly have community-level impacts on diversity, and these influences can be modulated by changing climate. Understanding gene by climate interactions such as these is important for assessing the impacts of climate change on forest diversity.